Pengaruh Disiplin Kerja dan Motivasi Kerja terhadap Produktivitas Pegawai pada Inspektorat Daerah Provinsi Sulawesi Selatan - Nurizzati Nurizzati; Uhud Darmawan Natsir; Zainal Ruma; Burhanuddin Burhanuddin; Rahmat Riwayat Abadi (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
This study aims to analyze the effect of work discipline and work motivation on employee productivity in the Auditor Division of the Regional Inspectorate of South Sulawesi Province. This research employed a quantitative approach using statistical analysis methods. The sample consisted of 57 respondents selected through purposive sampling techniques. Data were collected through questionnaires, and the analysis included validity and reliability testing, classical assumption testing, and multiple linear regression using the Statistical Package for the Social Sciences (SPSS) version 21. The findings revealed that both work discipline (X1) and work motivation (X2) simultaneously had a positive effect on employee productivity (Y). However, the partial test results indicated that work discipline did not have a significant effect on employee productivity, whereas work motivation had a significant positive effect. These findings suggest that work motivation plays a more dominant role in enhancing employee productivity compared to work discipline. Therefore, organizations are encouraged to strengthen motivational strategies through reward systems, recognition, and sustainable career development programs to optimize employee performance.